2017
DOI: 10.1111/jocn.13854
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of the efficacy of three different bowel preparation methods on the infectious complications following transrectal ultrasonography‐guided prostate biopsy in nursing practice

Abstract: Findings of this study provide useful evidence-based information for healthcare professionals. The application of combined preparation regimens of polyethylene glycol with povidone-iodine enema resulted in better improvement in the prevention of postbiopsy infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Mild complications can be resolved without treatment; however, serious ones may require surgical intervention (26). Common complications that occur during puncture are the vasovagal reflex, urethral hemorrhage, dysuria, acute urinary retention, hemospermia and infection (27). The vasovagal reflex manifests as palpitations, cold sweats and a drop in blood pressure, and a longer operation time increases the probability of developing this complication (28).…”
Section: Discussionmentioning
confidence: 99%
“…Mild complications can be resolved without treatment; however, serious ones may require surgical intervention (26). Common complications that occur during puncture are the vasovagal reflex, urethral hemorrhage, dysuria, acute urinary retention, hemospermia and infection (27). The vasovagal reflex manifests as palpitations, cold sweats and a drop in blood pressure, and a longer operation time increases the probability of developing this complication (28).…”
Section: Discussionmentioning
confidence: 99%
“… 4 Chiang et al 9 studied 3,694 Chinese prostate cancer patients and revealed that the rate of complications after prostate biopsy was 1.98%. A retrospective study 10 from China that included 1,130 patients who underwent prostate biopsy demonstrated that the overall infectious complications rate was 4.25% after prostate biopsy. These infectious complications included 26 (2.30%) cases of urinary tract infection, 22 (1.95%) cases of fever, but no cases of sepsis.…”
Section: Introductionmentioning
confidence: 99%